Kingdom of Lesotho : Poverty Reduction Strategy Paper, Prioritization, and Cost Matrix. (IMF Staff Country Reports; Country Report, 2006)
This Poverty Reduction Strategy Paper for the Kingdom of Lesotho presents a determined plan in pursuance of high and sustainable equity-based economic growth. It contains medium-term objectives and strategies to address the major challenges facing the country. These challenges include employment creation and income generation, and improving quality of and access to education and health services. Lesotho plans to deal boldly with its trading and investment partners by exploiting the opportunities inherent in the process of globalization under such mechanisms as the Africa Growth and Opportunities Act.